DESAIN PEMBELAJARAN BERBASIS PROYEK LOKAL DALAM KURIKULUM MERDEKA UNTUK MENGUATKAN PROFIL PELAJAR PANCASILA: SYSTEMATIC LITERATURE REVIEW SEBAGAI PANDUAN GURU PENDIDIKAN FORMAL - Dinda Syafitri; Yosi Mariana; Wening Patmi Rahayu; Andy Prasetyo Wati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Indonesia’s implementation of the Merdeka Curriculum necessitates that students not only achieve academic excellence but also possess the strong character embodied by the six dimensions of the Profile of Pancasila Students (P5). The effective strategy for achieving this goal is the integration of Project-Based Learning (PjBL) with local wisdom. This study aims to systematically review and synthesize existing research on Local Project-Based Learning Design in the Merdeka Curriculum to strengthen P5, particularly in formal education settings. Using a Systematic Literature Review (SLR) methodology, literature was selected from Google Scholar based on strict inclusion criteria from 2020–2025, resulting in the analysis of 7 relevant articles. The synthesis found that the application of local-based PjBL is highly adaptive across various educational levels, emphasizing contextual learning and direct involvement in community culture. This approach significantly contributes to strengthening P5 dimensions, especially Collaboration (Gotong Royong), Creativity, and Global Diversity (Kebhinekaan Global). The main supporting factor is the rich local culture, while the major obstacle is the varied competency of teachers in project management and authentic assessment. The findings confirm that Local Project-Based Learning serves as an ideal and visionary model for preparing Indonesian students who are characterized by Pancasila values, adaptive skills, and cultural roots. This SLR provides evidence-based guidance for formal education teachers in designing effective P5 projects.